Hubungan Perubahan Penggunaan Lahan dengan Limpasan Air Permukiman: Studi Kasus Kota Bogor - Pontoh, Nia Kurniasih (Center for Research and Community Services ITB, 2005)
Bogor City is one of cities function ing as counter magnet forJakarta, the capital city of Indonesia . There is a rapid land use change in Bogor that reduce the capacity to absorp water and increase the surface run -off water. Knowing that the position City of Bogor is located in center part of Ciliwung riverbasin and giving significant contribution to increasing the rate of flow o f river water. Run-off controlling is very important to decrease the flood threat for Jakarta and to increase the composit e of land water for City of Bogor itself. The study uses shift -share method analyzes comparing types and area of land use in different time . The result of study describe that the change of land -use will be influenced much by the condition of environment.Keywords: land-use change, run-off water, flood threat